Adsorption of hydrogen sulfide by biochars derived from pyrolysis of different agricultural/forestry wastes. (2nd January 2016) - Shang, Guofeng; Li, Qiwu; Liu, Liang; Chen, Ping; Huang, Xiamei
ABSTRACT: The characteristics and mechanisms of hydrogen sulfide (H2 S) adsorption on three different biochars derived from agricultural/forestry wastes through pyrolysis at various temperatures (100 to 500 ºC) were investigated. In this study, the H2 S breakthrough capacity was measured using a laboratory-characterized using pH and Fourier transform infrared spectroscopy analysis. The results obtained demonstrate that all biochars were effective in H2 S sorption. The sorption capacity of the biochar for H2 S removal is related to the pyrolysis temperature and pH of the surface. Certain threshold ranges of the pyrolysis temperature (from 100 to 500 ºC) and pH of the surface are presented. It also concluded that the sorption capacity (for removing H2 S) of rice hull-derived biochar is the largest in three biochars (camphor-derived biochar, rice hull-derived biochar, and bamboo-derived biochar). These observations will be helpful in designing biochar as engineered sorbents for the removal of H2 S. Implications : This paper focuses on the adsorption of hydrogen sulfide (H2 S) by biochars derived from wastes. The characteristics and mechanisms of hydrogen sulfide (H2 S) adsorption on three different boichars derived from agricultural/forestry wastes through pyrolysis at various temperatures were investigated. In this study, the H2 S breakthrough capacity was measured using laboratory characterization with pH and Fourier-transform infrared spectroscopy analysis. The results obtained demonstrate that all biochars were effective in H2 S sorption. The sorption capacity of the biochar for H2 S removal is related to the pyrolysis temperature and pH of the surface.